Surgical approach to hysterectomy and barriers to using minimally invasive methods. (15th May 2018) - Janda, Monika; Armfield, Nigel R.; Kerr, Gayle; Kurz, Suzanne; Jackson, Graeme; Currie, Jason; Page, Katie; Weaver, Edward; Yazdani, Anusch; Obermair, Andreas
Abstract : Minimally invasive approaches to hysterectomy have been shown to be safe, effective and have recovery advantages over open hysterectomy, yet in Australia 36% of hysterectomies are still conducted by open surgery. In 2006, a survey of Australian gynaecological specialists found the main impediment to increasing laparoscopic hysterectomy to be a lack of surgical skills training opportunities. We resurveyed specialists to explore contemporary factors influencing surgeons' approaches to hysterectomy; 258 (estimated 19%) provided analysable responses. Despite >50% of surveyed specialists wishing to practise laparoscopic hysterectomy in the future, lack of surgical skills, arising from the lack of training opportunities, remains the main impediment.